2007
DOI: 10.1038/sj.ejcn.1602683
|View full text |Cite
|
Sign up to set email alerts
|

Misreporting of dietary energy, protein, potassium and sodium in relation to body mass index in young Japanese women

Abstract: Objective: Although under-reporting of dietary intake is more common in persons with a high body mass index (BMI), it is not well known whether or not misreporting is selective for different foods (and hence energy and nutrients), particularly in nonWestern populations. We examined misreporting of dietary intake against biomarkers and its relation with BMI in young Japanese women. Design: Cross-sectional study. Subjects: A total of 353 female Japanese dietetic students aged 18-22 years (mean BMI: 21.4 kg/m 2 ,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(102 citation statements)
references
References 35 publications
5
97
0
Order By: Relevance
“…This was expected, as many researches indicated that obese underreport more (Tooze et al, 2007;Murakami et al, 2008). However, it is important to remark on the following: First, our study used DLW, which provides a valid determination of TEE for obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…This was expected, as many researches indicated that obese underreport more (Tooze et al, 2007;Murakami et al, 2008). However, it is important to remark on the following: First, our study used DLW, which provides a valid determination of TEE for obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the small proportion of SGA infants in the reference group of women in the 'rice, fish and vegetables' pattern, the risk of having a SGA infant for weight showed a higher OR and wide 95 % CI among women in the 'wheat products' pattern (multivariate OR 5·24, 95 % CI 1·13, 24·4), and the results should accordingly be interpreted with caution. Third, although we used a validated dietary assessment questionnaire, its ability to estimate total food and nutrient intake remains a serious concern, and incompleteness of the (32) , were classified as being SGA for weight, length or head circumference. † Adjusted for maternal age (,29, 29-31 and $ 32 years), parity (0 or $1), maternal height (cm), maternal pre-pregnancy BMI (kg/m 2 ), gestational weight gain (kg), week of gestation at baseline survey (weeks), cigarette smoking (never, former and current), change in diet in the previous 1 month (none or seldom, slight and substantial), dietary supplement use (yes and no), physical activity level (low and moderate or high), family structure (nuclear and expanded), occupation (housewife and outside work), family income (, 4 000 000, 4 000 000-5 999 999 and $6 000 000 yen/year), education (, 13, 13-14 and $15 years), season in which data at baseline were collected (spring, summer, autumn and winter), medical problems in pregnancy (yes and no) and baby's sex (boy and girl).…”
Section: Discussionmentioning
confidence: 99%
“…Food intake values were energy-adjusted using the energy-density model, i.e. g/4184 kJ, both to reduce the measurement error common with dietary assessment questionnaires (32,33) and to avoid biased grouping due to variation in body size and energy requirement (32) .…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…We excluded participants diagnosed with cold or influenza, and those who had taken multi-vitamin supplements at least once during the earlier month. In addition, we excluded participants whose 24-h urine collection or dietary records were considered as incomplete, with a collection time outside the 22-26-h range, urine volume o250 ml, creatinine excretion in relation to body weight outside the 10.8-25.2 mg/kg range (Stamler et al, 2003;Murakami et al, 2007), or extremely low or high energy intake (o2092 or 416 736 kJ/day) (Ministry of Health, Labour, and Welfare of Japan, 2005). After these screenings, 156 participants (26 male and 130 female) were found to be eligible.…”
Section: Participantsmentioning
confidence: 99%